(3JGQjN ehdO GdYdeGA hhaGJge ef Chd GdgLQI GdfHhjIs - (3GdnqQnHYj, CHh SdjeGf, eMeO Hf YHO Gddg Hf CMeO Hf QHjYI, J (B379 (3g`s ((3ESeGYjd Hf YHO GdYRjR GdRfcdhfjs)
(3ChdgG (B:s
(3CfHCfG GdTjN GdCejf gHI Gddg(B...(3Hf GdeYOd(B...(3fG CHh SdjeGf eMeO Hf YHO Gddg Hf RHQ GdQHYj GdMGaX bGd(B: (3GdMeO ddg MeOG cKjQG jHdZ QVGg hjhLH eRjOg(B...(3aeG cGf Yf CHj fYje GdaVd Hf Ocjf aMOKfGg YHO Gddg Hf eMeO GdHZhj MOKfG CMeO Hf EHQGgje Yf CHj fYje(B...s
(3BNQgG (B:s
...(3SfI NeS hKeGfjf hCQHYeGFI ajgG Jhaj CHh YHO Gddg eMeO Hf Ydj Hf CMeO Hf GdeHGQc(B...(3aj UaQ HOeTb(B. (3BNQ GdcJGHs
(3hjTJed GdcJGH Ydi Pjdj GdcJGfj hGdCcaGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B427s
(3GdCYdGe(B:(3L(B6(3,U(B225s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs